Rural resilience: The role of birth centers in the United States. Issue 4 (3rd December 2020) - Jolles, Diana; Stapleton, Susan; Wright, Jennifer; Alliman, Jill; Bauer, Kate; Townsend, Carla; Hoehn‐Velasco, Lauren
Abstract: Purpose: To explore the role of the birth center model of care in rural health and maternity care delivery in the United States. Methods: All childbearing families enrolled in care at an American Association of Birth Centers Perinatal Data Registry TM user sites between 2012 and 2020 are included in this descriptive analysis. Findings: Between 2012 and 2020, 88 574 childbearing families enrolled in care with 82 American Association of Birth Centers Perinatal Data Registry TM user sites. Quality outcomes exceeded national benchmarks across all geographic regions in both rural and urban settings. A stable and predictable rate of transfer to a higher level of care was demonstrated across geographic regions, with over half of the population remaining appropriate for birth center level of care throughout the perinatal episode of care. Controlling for socio demographic and medical risk factors, outcomes were as favorable for clients in rural areas compared with urban and suburban communities. Conclusions: Rural populations cared for within the birth center model of care experienced high‐quality outcomes. Health Policy Implications: A major focus of the United States maternity care reform should be the expansion of access to birth center models of care, especially in underserved areas such as rural communities.